Physicochemical Compatibility of Ceftolozane-Tazobactam with Parenteral Nutrition - Jan Thomas De Pourcq; Adria Riera; Laura Gras; Noe Garin; Maria Antònia Busquets; Joana Cardenete; Daniel Cardona; Pau Riera (MDPI AG, 2024)
Ceftolozane-tazobactam (CT) is used for the treatment of complicated infections and for multidrug-resistant strains of Pseudomonas aeruginosa and extended-spectrum beta-lactamase-producing enterobacteria. In certain cases, simultaneous administration of CT and parenteral nutrition (PN) may be required, but compatibility of Y-site co-administration is unknown. The aim of this study was to analyse the physicochemical compatibility of CT Y-site administered with PN. We evaluated a protocolized PN approach for critical patients in our center. We studied both bolus infusion (2 g ceftolozane/1 g tazobactam in 1 h) and continuous infusion (CI) (6 g ceftolozane/3 g tazobactam) strategies. Samples were visually observed against light, microscopically inspected, and pH was analysed using a pH meter. The mean lipid droplet diameter (MDD) was determined via dynamic light scattering. CT concentration was quantified using HPLC-HRMS. No alterations were observed through visual or microscopic inspection. Changes in pH were ≤0.2, and changes in osmolarity were less than 5%. MDD remained below 500 nm (284.5 ± 2.1 for bolus CT and 286.8 ± 7.5 for CI CT). CT concentrations at t = 0 h and t = 24 h remained within prespecified parameters in both infusion strategies. CT is physiochemically compatible with PN during simulated Y-site administration at the tested concentration and infusion rates.